ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH (K3) RISK IN THE CONSTRUCTION OF SAMPANG SOUTH RING ROAD (JLS) USING HAZID HIRA AND HAZOP METHODS - mukti, hazin; Zabadi, Fairus (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
Occupational Health and Safety (K3) is all engineering activities to support construction work in realizing the fulfillment of security, safety, health, and sustainability standards that ensure construction engineering safety, workforce safety and health, public safety, and environmental safety. This research was conducted to determine the risks of work accidents, identify technical implementation risk factors, and determine responses to the most dominant risks. The method used is HIRA, HAZID, and HAZOP. In HIRA, 4 dominant risk variables may occur during the construction of the South Ring Road (JLS) Sampang, namely: (X4.4), (X5.3), (X6.1), and (X6.2). To determine whether or not the variable data used to use the HAZID method is to use a preliminary questionnaire which is distributed before the main questionnaire. the correlation value of each variable is obtained or it is called the r count, then the r count can be compared with r table. To determine the risk response and recommendations that may occur using the HAZOP method is to use literature studies from previous journals as well as occupational safety and health standards. Thus, 19 recommendations for controlling the 4 dominant risks that may occur in the South Ring Road (JLS) Sampang project are obtained. Keywords: Occupational Safety and Health (K3), HAZID Method, HIRA Method, and HAZOP Method